Correlational Between Listening Habit to English Songs and Vocabulary Mastery - Hairani, Elisa; Lubis, Fitriadi; Siregar, Sri Rahmadhani (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study investigates the relationship between students' habits of listening to English songs and their vocabulary mastery. This research uses the quantitative method with a correlational research type. The sample of this study was 22 students of class XI MAN Tapanuli Selatan. Data were collected using questionnaires and tests and analyzed using the product moment test. The results of this study show that there is a correlation between the habit of listening to English songs and vocabulary mastery in the category with the value of rcount ˃ rtabel (0.442 ˃ 0.423). Therefore, the t-test shows that the alternative hypothesis (Ha) is accepted, and the null hypothesis (H0) is rejected.